Pediatric opsoclonus–myoclonus syndrome: the role of functional brain connectivity studies. (11th October 2016) - Gallerini, Simone; Marsili, Luca
Abstract : This commentary is on the original article by Chekroud et al. on pages98–104 of this issue.